Internalization of Islamic Worldview Culture of Learners throughMadrasah Climate in Madrasah Aliyah Swasta Amaliyah Sunggal - Kurniawan, Pandi; Siahaan, Amiruddin; Suryani, Ira (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This research aims to analyze the Internalization of Islamic Worldview Culture of Learners through Madrasah Climate at MASAmaliyah Sunggal. This research aims to reveal; 1) Planning ofInternalization of Islamic Worldview Culture of Students throughMadrasah Climate in MAS Amaliyah Sunggal; 2)Implementation/process of Internalization of Islamic WorldviewCulture of Students through Madrasah Climate in MAS AmaliyahSunggal; 3) Supporting and inhibiting factors of Internalization ofIslamic Worldview Culture of Students through Madrasah Climate in MAS Amaliyah Sunggal. This research uses a type of qualitativeresearch, with a critical discourse analysis approach, research datacollection is obtained by observation, interview and documentationtechniques. To check the validity of the data using triangulationtechniques, namely with credibilty, transferability, dependability andconfirmability. The results of this study there are three findings of thisstudy, namely: 1) Planning the Internalization of Islamic WorldviewCulture of Learners Through Madrasah Climate at MAS AmaliyahSunggal; 2) Implementation/process of Internalization of Islamic Worldview Culture of Learners through Madrasah Climate in MASAmaliyah Sunggal; 3) Supporting and inhibiting factors ofInternalization of Islamic Worldview Culture of Learners throughMadrasah Climate in MAS Amaliyah Sunggal the majorityexperienced a significant increase in two aspects, namely cognitiveand psychomotor aspects.